Individual differences in working memory capacity and the recall of predicted elements in the text - Braga Tomitch, Léda María (Lenguas Modernas, 2017)
This study investigates the relationship between reading ability, working memory capacity, and readers' use and recall of the mechanism of Prediction. Reading ability was measured by free recall and by comprehension questions, and working memory capacity was assessed by the Reading Span Test (Daneman and Carpenter 1980). Twelve Brazilian speakers of Pofuguese read texts containing the textual organizational aspect of Prediction and were asked to verbalize their thoughts while reading. An analysis of the verbai protocols indicates that better and weaker readers, also high and low span respectively, showed a different behavior when recalling the information from the texts. More proficient readers tended to recall both the predictive signal and all the predicted elements correctly, and could also recall more propositions from each text. Weaker readers, on the other hand, tended to simply disregard the predictive signal and recall only some of the predicted elements, and to recall less information than better readers.